The Nexus between Environmental Quality, Economic Growth, and Trade Openness in Saudi Arabia (1990-2017) - Daly, Saida; Abdouli, Mohamed (International Journal of Energy Economics and Policy, 2023)
In fact, this study endeavors to explore the relationship between CO2 emissions, trade, and economic growth using the simultaneous equation for Saudi Arabia over the period 1990–2017, using the VAR model and the impulse response functions to examine the relationship between these variables. Therefore, the obtained results showed that there is evidence of a bidirectional causality between CO2 emissions and economic growth. Moreover, the feedback hypothesis between trade openness and CO2 emissions is validated. Then, the retroaction hypothesis between economic growth and trade openness is identified. Furthermore, our results indicate economic growth impede environmental quality, while our empirical results have established crucial relationships that have important policy implications. However, it is mandatory for policy makers to develop economic, environmental and outside policies to promote economic growth and trade and improve the environmental quality.